Humanitarian law: the controversial historical construction of a universal moral - Soraya Nour Sckell (Janus.net, 2012)
Humanitarian law was conceived by legal and moral normativism founded on universal principles. Despite its undeniable universal moral content, its formulations and application methods are however the result of historical conflicts. This article aims to analyze how the universality of humanitarian law is produced by highly controversial conflicts. It is necessary to overcome the antagonism between an analysis that focuses on the moral undeniable value of humanitarian law by ignoring its controversies and an analysis that focuses on social antagonism questioning the achievability of the moral and universal value of humanitarian law. For this, we must consider that humanitarian law is a construction. It appears as autonomous and independent of power relationships, as based on the rationality of morality and thus worthy of universal recognition. Yet its development is only possible when one considers the historical roots of reason. It is only through political struggle that humanitarian law is realized in history. The aim of this paper is to analyze how the universal nature of humanitarian law is produced by highly controversial conflicts. Firstly, an analysis is offered on the universal but at the same controversial character in the codification of humanitarian law, recalling controversies around the creation of the Additional Protocols of 1977 (Section 1). Next, an analysis is given on the conflictual character of organizations supporting humanitarian law, taking in account conflicts between the Red Cross and Doctors Without Borders and controversies around the ambitions to pass from an humanitarian law to a right of humanitarian intervention (Section 2). Finally, a reflection is offered on how the theories of international relations that most appropriately grasp the universal nature of humanitarian law must be complemented by a "historical sociology of the universal" that embraces the conflicting historical dimension in the construction of the universal (Section 3).